450PSupportive care to control nausea and dizziness in malignant tumours: A systematic review. (24th November 2019) - Spiegel, R; Rothschild, S I; Kalla, R
Abstract: Background: Patients with malignant tumours may suffer from nausea as a side-effect of chemo-/radiotherapy. Antiemetic drugs can cause dizziness, which may lead to falls and decrease quality of life. Complementing research on painkiller-associated dizziness [1], we now focus on dizziness in association with antiemetic drugs. Methods: A systematic review is provided on dizziness in association with antiemetic drugs. A PubMed literature search was carried out for all articles in core clinical journals until 30 June 2019. Results: A total of 411 articles were identified. No study evaluated dizziness caused by antiemetic drugs as a primary endpoint. A focus on dizziness as a secondary endpoint revealed four studies with class 1a (meta-analysis) or 1b (randomized controlled trial) level of evidence (LoE). In cisplatin-based chemotherapy, there is LoE 1b that the 5-hydroxytryptamine 3 receptor antagonists (5-HT(3)RA) ondansetron [2] or the combination of tropisetron and dexamethasone [3] are better in terms of antiemetic potential and dizziness than metoclopramide [2] or metoclopramide plus dexamethasone plus diphenhydramine [3]. Among 5-HT(3)RAs, a meta-analysis with over 6000 patients [4] revealed that palonosetron had the lowest incidence of nausea and dizziness (LoE 1a). The neurokinin-1 receptor rolapitant was associated with less nausea than ondansetron plus dexamethasone in a randomized controlled trial (LoE 1b) including 454 patients and had a descriptively but not significantly higher incidence of dizziness [5]. Conclusions: 5-HT(3)RAs, particularly palonosetron, have an advantage with regard to antiemetic efficacy and frequency of reported dizziness when compared to metoclopramide [2-4]. The neurokinin-1 receptor rolapitant is a possible alternative [5]. References: 1. Spiegel R, et al. Ann Oncol. 2018 Oct;29(suppl_8):1793P. doi: 10.1093/annonc/mdy300.107 2. Tsavaris N, et al. Acta Oncol. 1995;34(2):243-6. doi: 10.3109/02841869509093962 3. Chua DT, et al. Br J Clin Pharmacol. 1996 May;41(5):403-8. doi: 10.1046/j.1365-2125.1996.03268.x 4. Popovic M, et al. Support Care Cancer. 2014 Jun;22(6):1685-97. doi: 10.1007/s00520-014-2175-6 5. Rapoport B, et al. Support Care Cancer. 2015 Nov;23(11):3281-8. doi: 10.1007/s00520-015-2738-1. Legal entity responsible for the study: The first author and the last author. Funding: Has not received any funding. Disclosure: S.I. Rothschild: Honoraria (institution), Honoraria for advisory boards to the institution: AbbVie; Honoraria (institution), Honoraria for advisory boards to the institution: AstraZeneca; Honoraria (institution), Honoraria for advisory boards to the institution: Boehringer Ingelheim; Honoraria (institution), Honoraria for advisory boards to the institution: BMS; Honoraria (institution), Honoraria for advisory boards to the institution: Eisai; Honoraria (institution), Honoraria for advisory boards to the institution: Eli Lilly; Honoraria (institution), Honoraria for advisory boards to the institution: Merck; Honoraria (institution), Honoraria for advisory boards to the institution: MSD; Honoraria (institution), Honoraria for advisory boards to the institution: Novartis; Honoraria (institution), Honoraria for advisory boards to the institution: Pfizer; Honoraria (institution), Honoraria for advisory boards to the institution: Roche; Honoraria (institution), Honoraria for advisory boards to the institution: Takeda; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Boehringer Ingelheim; Research grant / Funding (self): BMS; Research grant / Funding (self): Eisai. R. Kalla: Research grant / Funding (self), Grant #320030_173081: National Science Foundation of Switzerland. All other authors have declared no conflicts of interest.